2005
DOI: 10.1038/sj.bjc.6602859
|View full text |Cite
|
Sign up to set email alerts
|

Circadian function in patients with advanced non-small-cell lung cancer

Abstract: This study aimed to evaluate whether patients with advanced non-small-cell lung cancer experience disrupted rest -activity daily rhythms, poor sleep quality, weakness, and maintain attributes that are linked to circadian function such as fatigue. This report describes the rest -activity patterns of 33 non-small-cell lung cancer patients who participated in a randomised clinical trial evaluating the benefits of melatonin. Data are reported on circadian function, health-related quality of life (QoL), subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 27 publications
(23 reference statements)
1
59
2
Order By: Relevance
“…Earlier actigraph studies have reported abnormal circadian function in hospitalized cancer patients on chemotherapy when compared with outpatients in their home setting (29,43). Such investigations showed that daily sleep patterns were disturbed and translated into disruption of quality of life in patients with advanced lung cancer (43). Also, cancer-related fatigue in relapse-free patients with previous hematologic malignancies and depressed mood was related to decreased physical activity, rather than to anemia, endocrine, and immunologic alterations (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier actigraph studies have reported abnormal circadian function in hospitalized cancer patients on chemotherapy when compared with outpatients in their home setting (29,43). Such investigations showed that daily sleep patterns were disturbed and translated into disruption of quality of life in patients with advanced lung cancer (43). Also, cancer-related fatigue in relapse-free patients with previous hematologic malignancies and depressed mood was related to decreased physical activity, rather than to anemia, endocrine, and immunologic alterations (39).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these oscillating circuits are characterized by circadian periods and their synchronization integrates the many physiologic and behavioral processes required to meet the challenge of daily life (36,42). Earlier actigraph studies have reported abnormal circadian function in hospitalized cancer patients on chemotherapy when compared with outpatients in their home setting (29,43). Such investigations showed that daily sleep patterns were disturbed and translated into disruption of quality of life in patients with advanced lung cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…These include changes in endocrine rhythms (e.g., cortisol, melatonin, and prolactin secretion), metabolic processes (e.g., temperature and circulating protein levels), the immune system (e.g., levels of circulating leukocytes and neutrophils), and rest-activity patterns [73,[82][83][84][85][86][87][88][89]. Types of rhythm alteration include diminished amplitude, phase shifts, period changes, and erratic peaks and troughs.…”
Section: Thementioning
confidence: 99%
“…Table 1 summarizes the actigraphy data during putative daily wake spans and compares 33 cancer patients with a reference population of 35 normal adults. 72 These control data were obtained from a heterogeneous group of 35 adults who were 20 to 50 years old, who wore actigraphs for 3 days on the average, and had no known disease or chronic condition. We found that in all parameters, cancer patients were significantly different from the reference population.…”
Section: Cancer As a Cause Of Symptomatic Circadian Disruptionmentioning
confidence: 99%